KAMUTHE video microanalysis system for use in Brazil: translation, cross-cultural adaptation and evidence of validity and reliability - Gustavo Schulz Gattino (Health Psychology Report, 2016)
Background KAMUTHE is a video microanalysis system which observes preverbal communication within the music therapy setting. This system is indicated for children with autism spectrum disorder (ASD) or multiple disabilities. The purpose of this study was to translate, adapt to Brazilian Portuguese language and analyze some psychometric properties (reliability and validity evidence) of KAMUTHE administration in Brazil for individuals with ASD.